From Hobby to Global Tradition: The Early History of the Wonosobo Hot Air Balloon Festival and the Role of Kretek District (2004-2006) - Erma Eliyani; Bambang Rakhmanto (Historia, 2026)
The hot air balloon tradition in Wonosobo has evolved from a local pastime to a world-class cultural tourism festival, yet the Kretek District’s central role as a pioneer and guardian of this tradition remains largely unknown. This study aims to identify and analyze the history of Kretek in the development of the Wonosobo hot air balloon festival, describe the evolution of balloon flying practices over time, and document the individuals and communities who preserve the tradition. This study uses historical research methods. Although these methods generally rely on archives and written documents, this study gained important information from in-depth interviews with balloon flyers from the 1990s to 2008. These interviews not only serve as a complement to archival data but also serve as a primary source for understanding experiences, motivations, challenges, and innovations not formally recorded. The research reveals that Kretek has deep roots dating back to the Dutch era, inspired by the 1915 balloon landing, with Atmo Goper as a pioneer. This tradition has evolved significantly in materials, design (thanks to Mr. Kasuri and the “pendulumâ€), and ignition technique (the transition to coconut shells). Informal communities in Kretek preserve hereditary skills through collaboration.Â  At its peak, the 2005-2006 Wonosobo Balloon Festival was officially held, winning two MURI awards in 2006, confirming national recognition of this Kretek cultural heritage.